Noise pollution in access roads to the city of Chihuahua - Olague-Caballero, Cecilia Olivia (Universidad Autónoma de Tamaulipas, 2016)
Noise pollution is a problem of continuous public concern; major efforts are devoted to trying to abate it. Vehicular Traffic is a major source of noise pollution in urban areas. The main variables that influence the urban noise are the vehicles and the adjacent land use. The aim of this research was to quantify the noise level in three high traffic volume ways in Chihuahua city, Chihuahua, México: Chihuahua to Hermosillo, Sonora; Chihuahua to Ciudad Juárez, Chihuahua; and Chihuahua to Delicias, Chihuahua. For this 64 points of analysis were selected. The noise level was measured during peak hours. The index used was A-weighted equivalent continuous sound pressure level (Leq dB [A]), and the measurement unit was the decibel (dB). The results show that noise level ranged between 67.7 dB (A) and 75.5 dB (A), wich are above the permissible noise levels according to international standards. Using of berms, optimization of road surface, and sound barriers are suggested as adequate alternatives to mitigate the noise level at each point that exceed the maximum permitted levels during daytime.